1998
DOI: 10.1046/j.1440-1819.1998.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA DR2 and DQ1 frequency among narcoleptic patients in Hong Kong Chinese

Abstract: Key wordsNarcolepsy is a life-long crippling sleep disorder with significant physical and psychosocial impairments. Although its exact etiology and neuropathology is not clear, a strong association with specific human leucocyte antigen (HLA) subtype, particularly DR2 (DRwI5) and DQwl (DQw6), has been demonstrated across different ethnic groups including Caucasians and Japanese. The presence of 100% association with HLA DR2 in a series of Hong Kong Chinese narcoleptic patients has previously been reported. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
1
11
1
Order By: Relevance
“…16,17 In our group, some findings are in contrast to that found in other Asians, even of Hong Kong Chinese, in whom there was reported a 100% association of HLADR 2 and HLADQw6 with narcolepsy. 9,15 We found one child with sleepiness and cataplexy (but without SOREM), who was HLADR 2 and HLADQw6 negative. Allele studies showed that three patients tested negative for the HLADQB 1 *0602 marker, which has been believed to be the principal HLA marker of human narcolepsy.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…16,17 In our group, some findings are in contrast to that found in other Asians, even of Hong Kong Chinese, in whom there was reported a 100% association of HLADR 2 and HLADQw6 with narcolepsy. 9,15 We found one child with sleepiness and cataplexy (but without SOREM), who was HLADR 2 and HLADQw6 negative. Allele studies showed that three patients tested negative for the HLADQB 1 *0602 marker, which has been believed to be the principal HLA marker of human narcolepsy.…”
Section: Discussionmentioning
confidence: 85%
“…The incidence of HLA DR 2 and DQw6 in patients with narcolepsy will vary among ethnic groups. [9][10][11][12][13][14][15] Even in China, extrapolation of results from one region to another can be problematic, as the HLA distribution in the North has more evidence of Caucasian admixture, while in the South, the HLA distribution is more similar to population in Southeast Asia. 16,17 One limitation to address is our choice not to routinely perform PSG testing before the MSLT.…”
Section: Discussionmentioning
confidence: 99%
“…Forty patients (74%) had the ESS score ⩾14,19 whereas 30 patients (56%) had the UNS score ⩾14 7 11 12. UNS was sensitive in discriminating between cataplectic and non-cataplectic patients (table 1),7 11 whereas the two groups were comparable in ESS scores. Three non-cataplectic patients reported cataplexy-like symptoms in UNS but the presence of definite cataplexy in them was ruled out by further clinical interviews.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, these studies were further limited by their small sample population 6 – 10. Our previous studies in Hong Kong (southern) Chinese narcoleptics found out that all patients were HLA DR2- and DQ1-positive and the prevalence of narcolepsy in Hong Kong Chinese was 0.034% (95% CI 0.010% to 0.117%) 7 11. The aim of this study is to extend and update our report of the Hong Kong Chinese narcolepsy series.…”
mentioning
confidence: 74%
See 1 more Smart Citation